Use of hyaluronic acid preparations in the combination therapy of osteoarthritis - Yu. A. Olyunin (Современная ревматология)
The current recommendations for the pharmacotherapy of osteoarthritis (OA) primarily focus on analgesics and main concern is with the use of paracetamol and nonsteroidal anti-inflammatory drugs (NSAIDs). Intraarticular injections of first of all hyaluronic acid (HA) preparations that have proven to be effective in clinical practice are a promising treatment for OA. By taking into account the favorable safety profile of HA preparations, it may be suggested that these injections may be an acceptable alternative to NSAIDs or successfully used in combination with the latter. There have been recently the recommendations for the administration of HA preparations in OA treatment, which characterize the current practice of HA use for OA and had been prepared by a group of experts from 5 European countries. The experts consider that there is today rather solid evidence to demonstrate the efficacy of HA in mild and moderately severe knee OA; moreover, its effect is clinically significant in such patients. In the authors’ view, topical HA therapy should be a compulsory component of treatment for knee OA, since the alternative possibilities of therapy for this disease are limited. Although the optimal effect of HA is observed when it is applied in the early stage of OA, this treatment may be also useful in its late stage. HA should be regarded as an adjunct method that must be applied if surgery cannot be performed in these patients.